High-performance cement-based grouting material based on modified coral sand as well as preparation method and application thereof
By modifying coral sand and combining specific additives, high-performance cement-based grouting materials are prepared, which solves the problems of high transportation costs of traditional grouting materials in island and reef construction and has not been truly modified, and achieves the effects of high fluidity, early high strength, stable expansion and long-term durability.
Patent Information
- Application Number
- CN202510198875.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
In the prior art, high-performance cement-based grouting material using river sand as aggregate is expensive to transport during island and reef construction, and the modified coral sand has not been truly modified, which cannot effectively improve the fluidity, strength and durability of the grouting material.
By modifying the coral sand, high-performance cement-based grouting materials with large flow state, high strength, micro-expansion and high durability are prepared using raw materials such as cement, ion migration inhibitors, silicone hydrophobic agents, plastic expansion agents, and plastic expansion regulators.
It achieves high fluidity, early high strength, stable expansion performance and long-term durability of grouting materials, and is suitable for island and reef restoration and reinforcement and high-strength protection projects.
Smart Images

Figure CN119683945A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to grouting materials, and specifically to a high-performance cement-based grouting material based on modified coral sand, and a preparation method and application thereof. Background Art
[0002] In recent years, the importance of offshore island construction has increased, and the main infrastructure construction in my country's island and reef areas has been basically completed. Island construction is shifting towards high quality and high performance to improve living and production conditions, improve the performance of building facilities, and regularly maintain and reinforce them. There is an urgent need for high-performance grouting materials. Chinese invention patent application CN118359415A discloses a high-performance cement-based grouting material, but the patent uses river sand as aggregate, and the transportation cost from land to islands and reefs is huge, which is not conducive to island construction. Although Chinese invention patent application CN110272221A discloses a method for preparing modified coral sand concrete, it first exists and is used as concrete. The specific method is to crush the coral sand and then wrap it with cement slurry to form wrapped sand as aggregate. This is just to crush the coral sand and wrap it with cement slurry. In fact, the coral sand is not really modified, and the coral sand itself cannot be enhanced. It can only delay and restrict the infiltration of chloride ions in the coral sand to a certain extent, and the fluidity and expansion of the grouting material are not improved. The grouting material cannot be truly improved in terms of fluidity, strength, expansion rate and durability. It can be said that at present, the technology for preparing high-performance cement-based grouting material using modified coral sand as aggregate is still blank.
[0003] Therefore, it is necessary to develop a high-performance grouting material based on coral sand to fill the gap in this field and meet the urgent demand for high-performance grouting materials in repair and reinforcement and high-strength protection projects in the new development stage of island and reef construction. Summary of the invention
[0004] To solve the above problems, the first aspect of the present invention discloses a high-performance cement-based grouting material based on modified coral sand, which has the characteristics of high fluidity, high strength, micro-expansion and high durability, so as to fill the gap in this field.
[0005] The second aspect of the present invention discloses a method for preparing a high-performance cement-based grouting material, which can be made from local materials and is easy to implement.
[0006] The third aspect of the present invention discloses an application of a high-performance cement-based grouting material to meet the urgent demand for high-performance grouting materials in repair and reinforcement and high-strength protection projects in the new development stage of island and reef construction.
[0007] The above aspects of the present invention are achieved in this way:
[0008] The present invention first provides a high-performance cement-based grouting material based on modified coral sand, which is mixed with the following raw materials in terms of mass ratio:
[0009] Cement, 30-50 parts;
[0010] Modified coral sand, 40-60 parts;
[0011] Ion migration inhibitor, 5-15 parts;
[0012] Water reducing agent, 0.3~0.7 parts;
[0013] Rubber powder, 0.5~1.5 parts;
[0014] Defoaming agent, 0.05~0.15 parts;
[0015] Silicone water repellent, 0.08~0.12 parts;
[0016] Plastic expansion agent, 0.02~0.08 parts;
[0017] Plastic expansion regulator, 1.5~4.5 parts;
[0018] Mix with water, 9~12 parts.
[0019] The present invention uses local materials, and by using modified coral sand, it combines ion migration inhibitors, silicone hydrophobic agents, plastic expansion agents, plastic expansion regulators and necessary additives to obtain high-performance cement-based grouting materials with large fluidity, high strength, micro-expansion standards and high durability.
[0020] Preferably, the cement is one or more of Portland cement, ordinary Portland cement, sulphoaluminate cement, ferroaluminate cement and aluminate cement;
[0021] Preferably, the mixing water is one or more of seawater, desalinated seawater, fresh water, and rainwater naturally collected from the roofs of island and reef buildings.
[0022] Preferably, the raw material of the modified coral sand is obtained by crushing, ball milling and screening coral reef discs, with a maximum particle size of 1.25 mm, and the mass proportion of each particle size range is: 0.04 mm < particle size ≤ 0.16 mm accounts for 5-20%, 0.16 mm < particle size ≤ 0.315 mm accounts for 5-20%, 0.315 mm < particle size ≤ 0.63 mm accounts for 40-50%, and 0.63 mm < particle size ≤ 1.25 mm accounts for 30-40%.
[0023] Preferably, the prepared continuously graded coral sand raw material with a particle size of 0.04 mm to 1.25 mm is modified, specifically:
[0024] (1) Separately take cement, ion migration inhibitor and mixing water, and put the continuously graded coral sand raw material, cement, ion migration inhibitor and mixing water into a vacuum mixer in a mass ratio of 1:0.9:0.1:0.4;
[0025] (2) Turn on the vacuum mixer and stir for 3 to 5 minutes with the vacuum pump turned off, stirring at a low speed of 960 to 1200 r / h for 1 to 2 minutes and at a high speed of 7200 to 12000 r / h for 2 to 3 minutes. Stop stirring when the mixture is fully mixed;
[0026] (3) Turn on the vacuum pump and evacuate the device to 5% to 10% of the atmospheric pressure. Stir at a high speed of 7200 to 12000 r / h for 3 to 5 minutes. When the surface of the coral sand is fully coated by the cement slurry and relatively regular spherical particles are formed, stop stirring.
[0027] (4) Take out the mixture, spread it evenly and dry it in the sun for 24 hours. During this period, use a high-frequency vibration table to vibrate the mixture regularly to prevent it from sticking and affecting the uniformity of the modified coral sand.
[0028] (5) The dried mixture is screened with a sieve, and the target coral sand with a particle size range of 0.04 mm to 1.25 mm is the prepared modified coral sand.
[0029] Preferably, the ion migration inhibitor is one or more of hydrophobically modified ultrafine high-alumina slag powder, hydrophobically modified metakaolin, hydrophobically modified silica fume, and nano-silicon dioxide.
[0030] Preferably, the specific surface area of the hydrophobically modified ultrafine high-alumina slag powder is 1000-2500m 2 / kg, Al2O3 content is greater than 15%;
[0031] Preferably, the specific surface area of the hydrophobically modified metakaolin is 10000-15000m 2 / kg, Al2O3 content is greater than 40%;
[0032] Preferably, the specific surface area of the hydrophobically modified silica fume is 20000~30000m 2 / kg, SiO2 content is greater than 95%;
[0033] The specific surface area of the nano silicon dioxide is 160000~200000m 2 / kg, SiO2 content is greater than 99.5%.
[0034] Preferably, the water reducer is an early-strength high-efficiency polycarboxylate water reducer with a water reduction rate greater than 40%;
[0035] Preferably, the rubber powder is one or both of vinyl acetate and ethylene copolymer;
[0036] Preferably, the defoamer is one or both of a powdered silicone defoamer and a polyether defoamer;
[0037] Preferably, the active ingredient of the organosilicon water repellent is silane, which is in the form of an emulsion and has an effective content of 50%.
[0038] Preferably, the main component of the plastic expansion agent is azodicarbonamide;
[0039] Preferably, the plastic expansion regulator comprises a setting regulating component and an expansion component, wherein the setting regulating component includes one or more of calcium chloride, calcium formate, sodium carbonate, and sodium sulfate, and the expansion component includes one or more of calcium oxide type, calcium sulfoaluminate type, magnesium oxide type, and calcium oxide-calcium sulfoaluminate composite expansion agents.
[0040] The present invention also provides a method for preparing the high-performance cement-based grouting material, comprising:
[0041] (1) Add modified coral sand, cement, ion migration inhibitor, rubber powder, silicone water repellent and mixing water into a mixer at a mass ratio of 1:0.1:0.05:0.01:0.002:0.1;
[0042] (2) Stir at a low speed for 5 to 10 minutes until the surface of the modified coral sand is evenly coated with a layer of dry and thick hydrophobic slurry film;
[0043] (3) After standing for 5 to 10 minutes, observe that there is no visible water on the surface of the coral sand particles, add the remaining raw materials and continue stirring for 3 to 5 minutes, including: low-speed stirring time for 1 to 2 minutes, and high-speed stirring time for 2 to 3 minutes. After all materials are fully and evenly mixed, the high-performance cement-based grouting material is obtained.
[0044] The present invention also provides an application of the high-performance cement-based grouting material in island and reef construction, repair and reinforcement, and high-strength protection projects.
[0045] The beneficial effects of the present invention on the prior art are:
[0046] (1) The high-performance cement-based grouting material of the present invention has a large fluidity. The present invention first modifies the coral sand according to its loose, porous and easy-to-absorb characteristics. Before preparing the slurry, the coral sand is first modified, which is a pre-procedure for slurry preparation. Specifically, the slurry prepared by mixing cement, ion migration inhibitor and mixing water is filled into the pores of the coral sand and evenly wrapped on the surface of the coral sand to form relatively regular spherical particles to obtain modified coral sand, so as to reduce the absorption of mixing water by the coral sand during the stirring process and reduce the decrease in fluidity caused by the irregular shape of the coral sand; secondly, in the preparation process, by wrapping the surface of the modified coral sand with a hydrophobic clean slurry film, the effect of the modified coral sand on the fluidity of the grouting material is further reduced; thirdly, among the ion migration inhibitors used in the present invention, the ultrafine high-alumina slag powder, kaolin and silica fume are all hydrophobically modified, the water demand is reduced, and the fluidity of the grouting material is further improved; fourthly, the present invention uses a high-efficiency polycarboxylic acid water-reducing agent with a water reduction rate greater than 40%, and the fluidity of the grouting material is further improved.
[0047] (2) The high-performance cement-based grouting material of the present invention has high strength. First, the present invention modifies the coral sand, and the slurry is filled into the pores of the coral sand and then continues to hydrate and harden, so that the strength of the coral sand is greatly enhanced. The grading is designed, the stacking is tight, and the aggregate support effect is strong; secondly, the ion migration inhibitor used in the present invention improves the strength of the grouting material after hardening through the principle of the most dense stacking, and the ion migration inhibitor has a secondary hydration effect, and the hydration products gradually fill the internal pores of the grouting material, further improving the long-term strength of the grouting material; thirdly, the setting component in the plastic expansion regulator used in the present invention has an early strength effect, which can further improve the early strength of the grouting material; fourthly, the glue powder used in the present invention is dissolved in the mixing water to form a nanoemulsion, which can improve the microstructure of the grouting material at the nano level and improve the flexural strength of the grouting material; fifthly, the defoaming agent used in the present invention can effectively reduce the inclusion of bubbles in the preparation and stirring process of the high-performance cement-based grouting material, so that the grouting material is denser after hardening, and the strength is further effectively improved.
[0048] (3) The high-performance cement-based grouting material of the present invention has micro-expansion that meets the standard. The present invention uses a plastic expansion regulator. On the one hand, it can reasonably adjust the synergistic relationship between the gas generated by the plastic expansion agent and the strength development of the grouting material through the setting component, and design the early plastic expansion window period of the grouting material, so that the grouting material can retain the gas within 3 hours, reach a certain strength within 3-24 hours to constrain the gas to continue to expand, and avoid excessive vertical expansion rate in 3-24 hours, thereby achieving the early micro-expansion effect of the grouting material. On the other hand, the expansion component in the plastic expansion regulator can compensate for the shrinkage of the grouting material, and at the same time produce a synergistic effect with the plastic expansion agent. On the basis of the tiny pores generated by the plastic expansion agent, the product generated by the hydration reaction causes chemical expansion, further provides micro-expansion during the hardening process, and improves the density of the grouting material substrate, thereby further improving the strength. The present invention uses a plastic expansion regulator and provides a full curve of the vertical expansion rate, realizing controllable regulation of the vertical expansion rate.
[0049] (4) The high-performance cement-based grouting material of the present invention has the characteristics of high durability. First, the present invention uses modified coral sand, which greatly improves the density of the matrix after the grouting material is hardened, and at the same time can block the harmful ion outflow in the coral sand, thereby improving the durability; second, the ion migration inhibitor used in the present invention can inhibit the Cl - , SO4 2- ,Mg 2 + Harmful ions migrate and Al is dissolved during the hardening process of the grouting material. 3+ ions, avoiding the dissolution of hydration products in the grouting material matrix, and the secondary hydration of the ion migration inhibitor makes the grouting material matrix more compact and improves durability; thirdly, the cement used in the present invention can effectively prevent the corrosion of harmful substances such as acids and alkalis and improve durability by reasonably compounding aluminate cement, sulphoaluminate cement, and ferroaluminate cement. For example, the hydration of C3A (tricalcium aluminate) and C4A (tetracalcium aluminate) in aluminate cement can form stable compounds to resist sulfate corrosion; fourthly, the present invention uses a plastic expansion regulator to keep the grouting material in a micro-expansion state at all times, effectively preventing its shrinkage and cracking, avoiding the formation of channels for harmful ions to enter the matrix, and further improving the durability of the grouting material.
[0050] (5) The high-performance cement-based grouting material of the present invention has a high local material utilization rate. In combination with the current island and reef engineering construction situation, the present invention uses local materials to crush and screen coral reef plates to obtain coral sand instead of traditional aggregate quartz sand and river sand. Seawater can be used for mixing, saving transportation and raw material costs, saving economic costs, and effectively promoting the sustainable development of island and reef construction.
[0051] It should be understood that the implementation of any embodiment of the present invention does not mean that multiple or all of the above-mentioned beneficial effects must be possessed or achieved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0053] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment in size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.
[0054] Figure 1 The flowchart of the preparation process of a high-performance cement-based grouting material based on modified coral sand of the present invention is exemplified, wherein: the left side is the flowchart of the coral sand modification process, and the right side is the flowchart of the grouting material preparation process;
[0055] Figure 2A The diagram exemplarily shows the regulation mechanism of the vertical expansion rate window period by ordinary coral sand grouting material;
[0056] Figure 2B The diagram exemplarily shows the control mechanism of the vertical expansion rate window period of the modified coral sand grouting material of the present invention;
[0057] Figure 3 A schematic diagram exemplarily shows the regulating effect of the present invention on the vertical expansion rate window period.
[0058] In the various drawings, the same or corresponding reference numerals represent the same or corresponding parts. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the embodiments and drawings. Here, the illustrative embodiments of the present invention and their description are used to explain the present invention, but are not intended to limit the present invention.
[0060] It should be understood that the terms "include / comprise", "consist of..." or any other variations are intended to cover non-exclusive inclusion, so that a product, device, process or method that includes a series of elements includes not only those elements, but also may include other elements not explicitly listed when necessary, or also includes elements inherent to such product, device, process or method. In the absence of more restrictions, the elements defined by the sentence "include / comprise...", "consist of..." do not exclude the presence of other identical elements in the product, device, process or method that includes the elements.
[0061] The specific implementation and preferred embodiment of the high-performance cement-based grouting material based on modified coral sand proposed by the present invention are described in detail below.
[0062] The present invention first provides a high-performance cement-based grouting material based on modified coral sand, which is mixed by the following raw materials in a mass ratio: 30-50 parts of cement; 40-60 parts of modified coral sand; 5-15 parts of ion migration inhibitor; 0.3-0.7 parts of water reducer; 0.5-1.5 parts of glue powder; 0.05-0.15 parts of defoamer; 0.08-0.12 parts of organosilicon hydrophobic agent; 0.02-0.08 parts of plastic expansion agent; 1.5-4.5 parts of plastic expansion regulator; 9-12 parts of mixing water. The above-mentioned high-performance cement-based grouting material disclosed by the present invention, on the basis of large flow state, also has the advantages of high strength, micro expansion, high durability, etc., can be made of local materials, and meets the urgent demand for high-performance grouting materials in repair and reinforcement, high-strength protection engineering after the island and reef engineering construction enters a new development stage.
[0063] In some embodiments, the cement is preferably one or more combinations of Portland cement, ordinary Portland cement, sulphoaluminate cement, ferroaluminate cement and aluminate cement. The cement used in the present invention can effectively prevent corrosion by harmful substances such as acids and alkalis and improve durability by reasonably compounding aluminate cement, sulphoaluminate cement and ferroaluminate cement. For example, C3A (tricalcium aluminate) and C4A (tetracalcium aluminate) in aluminate cement can form stable compounds after hydration to resist sulfate corrosion.
[0064] In some embodiments, the ion migration inhibitor is one or more of hydrophobically modified ultrafine high-alumina slag powder, hydrophobically modified metakaolin, hydrophobically modified silica fume, and nano-silica.
[0065] In some specific embodiments, the specific surface area of the hydrophobically modified ultrafine high-alumina slag powder is 1000-2500 m 2 / kg, Al2O3 content is greater than 15%; the specific surface area of hydrophobically modified metakaolin is 10000~15000m 2 / kg, Al2O3 content is greater than 40%; the specific surface area of hydrophobic modified silica fume is 20000~30000m 2 / kg, SiO2 content is greater than 95%; the specific surface area of nano silicon dioxide is 160000~200000m 2 / kg, SiO2 content is greater than 99.5%.
[0066] The ultrafine high-alumina slag powder, metakaolin, and silica fume in the present invention are all treated with hydrophobic modification, and the water requirement is reduced, and the fluidity of the grouting material is further improved. When the technology of the present invention is not used, if the same large flow state is to be achieved, more water reducing agent needs to be added or the water consumption needs to be increased, and the mechanical properties and durability of the grouting material will be greatly reduced, and the grouting material will be super slow setting, and the plastic expansion agent will not work up to the standard, resulting in the vertical expansion rate not meeting the national standard requirements.
[0067] Furthermore, the ion migration inhibitor of the present invention inhibits Cl - , SO4 2- ,Mg 2 + Harmful ions migrate and Al is dissolved during the hardening process of the grouting material. 3+ Ions avoid the dissolution of hydration products in the grouting material matrix. The secondary hydration of the ion migration inhibitor makes the grouting material matrix denser and more durable. In addition, through the principle of the most dense stacking, the strength of the grouting material is improved after hardening, and the ion migration inhibitor has a secondary hydration effect. The hydration products gradually fill the internal pores of the grouting material, further improving the long-term strength of the grouting material.
[0068] In some embodiments, the raw materials of modified coral sand are obtained by crushing, ball milling and screening coral reef discs, and the maximum particle size is 1.25 mm. The mass proportion of each particle size range is: 0.63 mm < particle size ≤ 1.25 mm accounts for 30~40%, 0.315 mm < particle size ≤ 0.63 mm accounts for 40~50%, 0.16 mm < particle size ≤ 0.315 mm accounts for 5~20%, and 0.04 mm < particle size ≤ 0.16 mm accounts for 5~20%; the apparent density is 2350~2450 kg / m³, and the bulk density is 1005~1065 kg / m³.
[0069] Furthermore, the present invention first modifies the coral sand raw material before preparing the slurry, that is, the prepared continuously graded coral sand raw material with a particle size of 0.04 mm to 1.25 mm is modified, which is a pre-procedure for slurry preparation. Figure 1 As shown, the following steps are included:
[0070] (1) Separately take cement, ion migration inhibitor and mixing water, and put the continuously graded coral sand raw material, cement, hydrophobic modified silica fume and mixing water into a vacuum mixer in a mass ratio of 1:0.9:0.1:0.4; it is easy to understand that the cement, ion migration inhibitor and mixing water taken at this time have nothing to do with the main materials for preparing the slurry, and are materials taken separately for the purpose of modification. The specific amount taken is based on the coral sand raw material and is added in proportion;
[0071] (2) Turn on the vacuum mixer and stir for 3 to 5 minutes with the vacuum pump turned off, including 1 to 2 minutes of low-speed stirring (960 to 1200 r / h) and 2 to 3 minutes of high-speed stirring (7200 to 12000 r / h). Stop stirring when the mixture is fully mixed;
[0072] (3) Turn on the vacuum pump and evacuate the device to 5% to 10% of the atmospheric pressure. Perform high-speed stirring (7200 to 12000 r / h) for 3 to 5 minutes. When the surface of the coral sand is fully coated by the cement slurry and relatively regular spherical particles are formed, stop stirring.
[0073] (4) Take out the mixture, spread it evenly and dry it in the sun for 24 hours. During this period, use a high-frequency vibration table to vibrate the mixture regularly to prevent it from sticking and affecting the uniformity of the modified coral sand.
[0074] (5) The dried mixture is screened with a sieve, and the target coral sand with a particle size range of 0.04 mm to 1.25 mm is the prepared modified coral sand.
[0075] The present invention first modifies the coral sand for its looseness, porosity and easy water absorption. The principle of the modification method is to use negative pressure to absorb cement paste, which is different from ordinary immersion or granulation, so that the cement paste hardens and strengthens. Specifically, a negative pressure environment is formed by using a vacuum mixer to fill the slurry made of cement, hydrophobic modified silica fume and mixing water into the pores of the coral sand, and evenly wrap it on the surface of the coral sand to form relatively regular spherical particles, so as to reduce the coral sand from absorbing mixing water during the stirring process and reduce the decrease in fluidity caused by the irregular shape of the coral sand. Secondly, in the preparation process, by wrapping the hydrophobic net slurry film on the surface of the modified coral sand, its influence on the fluidity of the grouting material is further reduced, thereby obtaining a large flow state. Moreover, after the slurry is filled into the pores of the coral sand, it continues to hydrate and harden, and the strength of the coral sand is greatly enhanced. The gradation is designed, the stacking is tight, and the aggregate support effect is strong, thereby obtaining high strength. In addition, through the modification of the coral sand, the density of the matrix after the grouting material is hardened is greatly improved, and the durability is improved.
[0076] In some embodiments, the water reducer is an early-strength high-efficiency polycarboxylate water reducer with a water reduction rate greater than 40%.
[0077] In some embodiments, the rubber powder is one or both of vinyl acetate and ethylene copolymer. The rubber powder is dissolved in the mixing water to form a nanoemulsion, which can improve the microstructure of the grouting material at the nano level and increase the flexural strength of the grouting material, thereby obtaining high strength.
[0078] In some embodiments, the defoamer is one or both of a powdered silicone defoamer and a polyether defoamer. The defoamer can effectively reduce the introduction of bubbles during the preparation and mixing of high-performance cement-based grouting materials, making the grouting materials denser after hardening, and further effectively improving the strength.
[0079] In some embodiments, the active ingredient of the organosilicon hydrophobic agent is silane, which is in the form of an emulsion and has an effective content of 50%. The organosilicon hydrophobic agent is used to prepare hydrophobic slurry. By preparing the hydrophobic slurry and coating the surface of the modified coral sand with a hydrophobic slurry film, the effect on the fluidity of the grouting material is further reduced, thereby obtaining a large flow state.
[0080] In some embodiments, the main component of the plastic expansion agent is azodicarbonamide. The plastic expansion agent plays a decisive role in the vertical expansion rate of the grouting material within 24 hours in the early stage. Its mechanism of action is to react in an alkaline environment to produce nitrogen. At the same time, the matrix strength is reasonable, and the gas will not escape due to too low strength, nor will the gas be sealed due to too high strength.
[0081] In some embodiments, the plastic expansion regulator comprises a setting regulating component and an expansion component, wherein the setting regulating component comprises one or more of calcium chloride, calcium formate, sodium carbonate, and sodium sulfate; and the expansion component comprises one or more of calcium oxide type, calcium sulfoaluminate type, magnesium oxide type, and calcium oxide-calcium sulfoaluminate composite type expansion agents. The present invention uses a plastic expansion regulator to keep the grouting material in a micro-expansion state at all times, effectively preventing it from shrinking and cracking, avoiding the formation of channels for harmful ions to enter the matrix, and further improving the durability of the grouting material.
[0082] It should be noted that the plastic expansion regulator used in the present invention has an early strength effect and can improve the early strength of the grouting material. In addition, the present invention has the characteristics of micro-expansion reaching the standard and the expansion process being designable, as shown in Figure 2, Figure 3 As shown, the present invention uses a plastic expansion regulator, which can reasonably adjust the synergistic relationship between the gas generated by the plastic expansion agent and the strength development of the grouting material through the setting adjustment component. Figure 2BAs shown in the figure, the early plastic expansion window of the grouting material is designed so that the grouting material can retain gas within 3 hours, reach a certain strength within 3-24 hours to restrain the gas from continuing to expand, and avoid excessive vertical expansion rate in 3-24 hours, thereby achieving the early micro-expansion effect of the grouting material. On the other hand, the expansion component in the plastic expansion regulator can compensate for the shrinkage of the grouting material, and at the same time, synergize with the plastic expansion agent. On the basis of the tiny pores produced by the plastic expansion agent, the products generated by the hydration reaction cause chemical expansion, further provide micro-expansion during the hardening process, and improve the density of the grouting material base material, thereby further improving the strength. Figure 2A As shown, under the premise of large flow state, the coral sand grouting material without the technology of the present invention often has super slow setting phenomenon due to excessive use of water reducing agent and mixing water, which will cause the window period for the plastic expansion agent to exert its expansion efficiency to be delayed, which is manifested as the gas escape generated by the plastic expansion agent within 3 hours, resulting in too small vertical expansion rate. Within 3-24 hours, due to the large amount of ineffective consumption of plastic expansion agent and the shrinkage of cementitious materials, effective expansion can no longer be generated. At this time, if the amount of plastic expansion agent is increased, the 3h vertical expansion rate will not meet the standard, and the 3-24h vertical expansion rate will exceed the standard.
[0083] In some embodiments, the mixing water is one or more of seawater, desalinated seawater, fresh water, and rainwater naturally collected from the roof of island and reef buildings. In the present invention, the mixing water is obtained locally, saving the cost of transportation and raw materials.
[0084] The present invention also provides a method for preparing a high-performance cement-based grouting material based on modified coral sand, such as Figure 1 As shown, including:
[0085] (1) Add modified coral sand, cement, ion migration inhibitor, rubber powder, silicone water repellent and mixing water into a mixer at a mass ratio of 1:0.1:0.05:0.01:0.002:0.1;
[0086] (2) Stir at a low speed (960-1200 r / h) for 5-10 min until the surface of the modified coral sand is evenly coated with a layer of dry and thick hydrophobic slurry film;
[0087] (3) After standing for 5 to 10 minutes, observe that there is no visible water on the surface of the coral sand particles. Add the remaining raw materials and continue stirring for 3 to 5 minutes. The low-speed stirring time (960 to 1200 r / h) is 1 to 2 minutes, and the high-speed stirring time (7200 to 12000 r / h) is 2 to 3 minutes. After all the materials are fully and evenly mixed, a high-performance cement-based grouting material based on modified coral sand is obtained.
[0088] It should be noted that, in the preparation process, the hydrophobic clean slurry film is coated on the surface of the modified coral sand to further reduce its influence on the fluidity of the grouting material. The present invention uses modified coral sand to greatly improve the density of the matrix of the grouting material after hardening, and improves the durability.
[0089] Example 1
[0090] The materials prepared in this embodiment have the following components in terms of mass: 40 parts of cement, 50 parts of modified coral sand, 10 parts of ion migration inhibitor, 0.5 parts of water reducer, 0.5 parts of rubber powder, 0.1 parts of defoamer, 0.1 parts of silicone hydrophobic agent, 0.04 parts of plastic expansion agent, 3 parts of plastic expansion regulator, and 10 parts of mixing water.
[0091] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0092] Example 2
[0093] The materials prepared in this embodiment have the following components in terms of mass: 30 parts of cement, 60 parts of modified coral sand, 10 parts of ion migration inhibitor, 0.4 parts of water reducer, 0.4 parts of rubber powder, 0.05 parts of defoamer, 0.12 parts of silicone hydrophobic agent, 0.02 parts of plastic expansion agent, 2 parts of plastic expansion regulator, and 9 parts of mixing water.
[0094] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0095] Example 3
[0096] The materials prepared in this embodiment have the following components in terms of mass: 50 parts of cement, 40 parts of modified coral sand, 10 parts of ion migration inhibitor, 0.7 parts of water reducer, 1 part of rubber powder, 0.12 parts of defoamer, 0.08 parts of silicone hydrophobic agent, 0.06 parts of plastic expansion agent, 4 parts of plastic expansion regulator, and 12 parts of mixing water.
[0097] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0098] Example 4
[0099] The materials prepared in this embodiment have the following components in terms of mass: 45 parts of cement, 40 parts of modified coral sand, 15 parts of ion migration inhibitor, 0.6 parts of water reducer, 0.8 parts of rubber powder, 0.1 parts of defoamer, 0.08 parts of silicone hydrophobic agent, 0.08 parts of plastic expansion agent, 3.5 parts of plastic expansion regulator, and 11 parts of mixing water.
[0100] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0101] Comparative Example 1
[0102] The materials prepared in this comparative example have the following components in proportion by mass: 40 parts of cement, 50 parts of coral sand, 10 parts of ion migration inhibitor, 0.5 parts of water reducer, 0.5 parts of rubber powder, 0.1 parts of defoamer, 0.2 parts of silicone hydrophobic agent, 0.04 parts of plastic expansion agent, 3 parts of plastic expansion regulator, and 10 parts of mixing water.
[0103] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0104] The difference between this comparative example and Example 1 is that the coral sand is not modified, and the amount of water reducing agent is increased to meet the large flow performance.
[0105] Comparative Example 2
[0106] The materials prepared in this comparative example have the following components in proportion by mass: 40 parts of cement, 50 parts of modified coral sand, 10 parts of ion migration inhibitor, 0.5 parts of water reducer, 0.5 parts of rubber powder, 0.1 parts of defoamer, 0.2 parts of silicone hydrophobic agent, 0.04 parts of plastic expansion agent, 3 parts of plastic expansion regulator, and 10 parts of mixing water.
[0107] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0108] The difference between this comparative example and Example 1 is that the aggregate is not coated with a hydrophobic slurry film during stirring, and the amount of water reducing agent is increased to meet the large flow performance.
[0109] Comparative Example 3
[0110] The materials prepared in this embodiment have the following components in terms of mass: 40 parts of cement, 50 parts of modified coral sand, 10 parts of ion migration inhibitor, 0.5 parts of water reducer, 0.5 parts of rubber powder, 0.1 parts of defoamer, 0.2 parts of silicone hydrophobic agent, 0.04 parts of plastic expansion agent, 3 parts of plastic expansion regulator, and 10 parts of mixing water.
[0111] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0112] The only difference between this comparative example and Example 1 is that no early strength agent is added.
[0113] Comparative Example 4
[0114] The materials prepared in this embodiment have the following components in terms of mass: 40 parts of cement, 50 parts of modified coral sand, 10 parts of ion migration inhibitor, 0.5 parts of water reducer, 0.5 parts of rubber powder, 0.1 parts of defoamer, 0.2 parts of silicone hydrophobic agent, 0.04 parts of plastic expansion agent, 3 parts of plastic expansion regulator, and 10 parts of mixing water.
[0115] The cement consists of 80% P·II 52.5 grade silicate cement, 10% ferroaluminate cement and 10% aluminate cement; the ion migration inhibitor consists of 40% hydrophobically modified ultrafine high-alumina slag powder, 32% hydrophobically modified metakaolin, 27% hydrophobically modified silica fume and 1% nano-silicon dioxide; the plastic expansion regulator consists of 33% setting adjustment component and 67% expansion component, wherein the setting adjustment component consists of 50% sodium carbonate and 50% calcium formate, and the expansion component is a calcium oxide-calcium sulfoaluminate composite expansion agent.
[0116] The difference between this comparative example and Example 1 is that the coral sand is not modified, the hydrophobic slurry is not prepared during stirring, the early strength agent is not added, and the amount of the water reducing agent is increased to meet the large flow performance.
[0117] In order to verify the performance of the high performance cement-based grouting material based on modified coral sand proposed in the present invention, Figure 1 The high-performance cement-based grouting material of the modified coral sand of the present invention is prepared according to the operation steps and reference specifications, and the performance of the obtained grouting material is tested. The test results are shown in Table 1.
[0118] Table 1 Grouting material properties for each case
[0119]
[0120] Note: According to GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials", the vertical expansion rate of cement-based grouting materials must meet the following requirements: 3h vertical expansion rate 0.1%~3.5%, and the difference between 24h and 3h vertical expansion rates 0.02%~0.50%.
[0121] As can be seen from Table 1, the high-performance cement-based grouting material based on modified coral sand proposed in the present invention has high fluidity, an initial fluidity of more than 350, a 30-min fluidity of no less than 320, high early strength (1d compressive strength greater than 20MPa), and a 28d compressive strength of more than 120MPa. The expansion performance is stable and durable, and the 3h vertical expansion rate and the difference between the 24h and 3h vertical expansion rates are ten times or even dozens of times that of the comparative example. The raw materials can be obtained locally, and are suitable for repair and reinforcement, and high-strength protection projects.
[0122] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
[0123] Although several specific implementation details are included in the above discussion, these should not be construed as limiting the scope of the present invention. Certain features described in the context of separate embodiments may also be implemented in a single implementation in combination. On the contrary, the various features described in the context of a single implementation may also be implemented in multiple implementations individually or in any suitable sub-combination.
Claims
1. A high-performance cement-based grouting material based on modified coral sand, characterized in that: The following raw materials are mixed according to mass ratio: Cement, 30-50 parts; Modified coral sand, 40-60 parts; Ion migration inhibitor, 5-15 parts; Water reducing agent, 0.3~0.7 parts; Rubber powder, 0.5~1.5 parts; Defoaming agent, 0.05~0.15 parts; Silicone water repellent, 0.08~0.12 parts; Plastic expansion agent, 0.02~0.08 parts; Plastic expansion regulator, 1.5~4.5 parts; Mix with water, 9~12 parts.
2. The high performance cement-based grouting material according to claim 1, characterized in that: The cement is one or more of Portland cement, ordinary Portland cement, sulphoaluminate cement, ferroaluminate cement and aluminate cement; and / or The mixing water is one or more of seawater, desalinated seawater, fresh water, and rainwater naturally collected from the roofs of island and reef buildings.
3. The high performance cement-based grouting material according to claim 1, characterized in that: The raw materials of the modified coral sand are obtained by crushing, ball milling and screening coral reef discs, with a maximum particle size of 1.25 mm. The mass proportion of each particle size range is: 0.04 mm < particle size ≤ 0.16 mm accounts for 5-20%, 0.16 mm < particle size ≤ 0.315 mm accounts for 5-20%, 0.315 mm < particle size ≤ 0.63 mm accounts for 40-50%, and 0.63 mm < particle size ≤ 1.25 mm accounts for 30-40%.
4. The high performance cement-based grouting material according to claim 3, characterized in that: The obtained continuously graded coral sand raw material with a particle size of 0.04 mm to 1.25 mm is modified as follows: (1) Separately take cement, ion migration inhibitor and mixing water, and put the continuously graded coral sand raw material, cement, ion migration inhibitor and mixing water into a vacuum mixer in a mass ratio of 1:0.9:0.1:0.4; (2) Turn on the vacuum mixer and stir for 3 to 5 minutes with the vacuum pump turned off, stirring at a low speed of 960 to 1200 r / h for 1 to 2 minutes and at a high speed of 7200 to 12000 r / h for 2 to 3 minutes. Stop stirring when the mixture is fully mixed; (3) Turn on the vacuum pump and evacuate the device to 5% to 10% of the atmospheric pressure. Stir at a high speed of 7200 to 12000 r / h for 3 to 5 minutes. When the surface of the coral sand is fully coated by the cement slurry and relatively regular spherical particles are formed, stop stirring. (4) Take out the mixture, spread it evenly and dry it in the sun for 24 hours. During this period, use a high-frequency vibration table to vibrate the mixture regularly to prevent it from sticking and affecting the uniformity of the modified coral sand. (5) The dried mixture is screened with a sieve, and the target coral sand with a particle size range of 0.04 mm to 1.25 mm is the prepared modified coral sand.
5. The high performance cement-based grouting material according to claim 1, characterized in that: The ion migration inhibitor is one or more of hydrophobically modified ultrafine high-alumina slag powder, hydrophobically modified metakaolin, hydrophobically modified silica fume, and nano-silicon dioxide.
6. The high performance cement-based grouting material according to claim 5, characterized in that: The specific surface area of the hydrophobically modified ultrafine high-alumina slag powder is 1000-2500m 2 / kg, Al2O3 content greater than 15%; and / or The specific surface area of the hydrophobically modified metakaolin is 10000-15000m 2 / kg, Al2O3 content greater than 40%; and / or The specific surface area of the hydrophobically modified silica fume is 20000-30000m 2 / kg, SiO2 content greater than 95%; and / or The specific surface area of the nano silicon dioxide is 160000~200000m 2 / kg, SiO2 content is greater than 99.5%.
7. The high performance cement-based grouting material according to claim 1, characterized in that: The water reducing agent is an early-strength high-efficiency polycarboxylate water reducing agent with a water reducing rate greater than 40%; and / or The rubber powder is one or both of vinyl acetate and ethylene copolymer; and / or The defoamer is one or both of a powdered silicone defoamer and a polyether defoamer; and / or The organic silicon water repellent agent has silane as an effective ingredient and is in the form of an emulsion with an effective content of 50%.
8. The high performance cement-based grouting material according to claim 1, characterized in that: The main component of the plastic expansion agent is azodicarbonamide; and / or The plastic expansion regulator comprises a setting regulating component and an expansion component, wherein the setting regulating component comprises one or more of calcium chloride, calcium formate, sodium carbonate, and sodium sulfate, and the expansion component comprises one or more of calcium oxide type, calcium sulfoaluminate type, magnesium oxide type, and calcium oxide-calcium sulfoaluminate composite expansion agents.
9. A method for preparing the high-performance cement-based grouting material according to any one of claims 1 to 8, comprising: (1) Add modified coral sand, cement, ion migration inhibitor, rubber powder, silicone water repellent and mixing water into a mixer at a mass ratio of 1:0.1:0.05:0.01:0.002:0.1; (2) Stir at a low speed for 5 to 10 minutes until the surface of the modified coral sand is evenly coated with a layer of dry and thick hydrophobic slurry film; (3) After standing for 5 to 10 minutes, observe that there is no visible water on the surface of the coral sand particles, add the remaining raw materials and continue stirring for 3 to 5 minutes, including: low-speed stirring time for 1 to 2 minutes, and high-speed stirring time for 2 to 3 minutes. After all materials are fully and evenly mixed, the high-performance cement-based grouting material is obtained.
10. Use of the high-performance cement-based grouting material according to any one of claims 1 to 8 in island and reef construction, repair and reinforcement, and high-strength protection projects.
Citation Information
Patent Citations
Preparation method of modified coral sand concrete
CN110272221A
High-performance cement-based grouting material and preparation method thereof
CN118359415A
Preparation method of micro-expansive high-intensity grouting material
CN108751857A
Cement-based grouting material for ocean engineering and preparation method thereof
CN109650806A
Coral sand breathable impermeable sand
CN112321261A
Cited By
Green and environment-friendly scattered and solid composite pile system for treating coral sand roadbed and construction method
CN121161677A